Application of the servqual method for evaluation of PDAM service quality - Adelia Alviyana; Astrilyana Astrilyana (Institute of Computer Science (IOCS), 2023)
PDAM Tirta Rangga Ciasem is a regional company responsible for managing and meeting the clean water needs of the community in Ciasem District. Improving the quality of service is one of the marketing strategies that emphasizes the fulfillment of customer needs. Evaluation of customer satisfaction with the management and fulfillment of clean water must be carried out as a form of service quality assessment. Using the Service Quality (Servqual) method, an evaluation questionnaire is given to customers with evaluation criteria based on reliability, assurance, tangibility, empathy and responsiveness. Based on the results of the calculation of the population and sample requirements, 129 samples were taken from a total of 190 existing customers. From the results of collecting questionnaire data completed by 129 samples, data processing was performed, which found that the existing GAP value showed that the majority of PDAM customer communities were satisfied with the current service. With the best GAP of 0.51 which shows the service and attitude of the officer is very good while the worst GAP is 0.82 which shows deficiencies in the taste and aroma of water provided in PDAM Tirta Rangga Ciaseme service.